2018
DOI: 10.1097/ncc.0000000000000563
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Women’s Breast Health–Seeking Behaviors

Abstract: The study findings provided deeper understanding about the effective factors related to a husband's role in motivating a wife to practice breast cancer prevention. These new findings are relevant for health educators and practitioners to develop culturally based interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In 1 study conducted on Iranian women with breast cancer, the husbands' behavior was identified as the major source of support for help-seeking behaviors. Family cohesion and love between the couples were strong predictors of the husbands' supportive behaviors 30 . Another study in Iran has shown that husbands' support may improve the well-being of women with breast cancer 29 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In 1 study conducted on Iranian women with breast cancer, the husbands' behavior was identified as the major source of support for help-seeking behaviors. Family cohesion and love between the couples were strong predictors of the husbands' supportive behaviors 30 . Another study in Iran has shown that husbands' support may improve the well-being of women with breast cancer 29 .…”
Section: Discussionmentioning
confidence: 95%
“…At the same time, they should also carry out other responsibilities such as housekeeping and childcare. Sacrificing, prioritizing family health, and striving to preserve the integrity of the family are the common features of Iranian women 30 . Because family members are the most important source of social support for Iranian women, efforts are needed to reduce women's self-sacrifice in the family.…”
Section: Discussionmentioning
confidence: 99%
“…The sample of 17 men and 11 women reported an average of 28 years between the risk period of this virus and the first test. These data show that risk awareness does not necessarily lead to action [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Research Backgroundmentioning
confidence: 99%
“…After mentioning some types of diseases and the work that has been done in the past to diagnose them using neural networks, they introduced the basic steps for medical diagnosis using neural networks. They concluded that neural networks are a powerful tool to help doctors diagnose diseases [1][2][3][4][5][6][7][8][9].…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation